Hak Atas Informasi, Edukasi Dan Pelayanan Kesehatan Terhadap Masyarakat Adat Di Maluku Selama Pandemi Covid-19 - Arman Anwar; Richard Marsilio Waas (Faculty of Law, Universitas Pattimura, 2021)
The main objective of this research is to determine the fulfillment of the right to information, education and health services to indigenous peoples carried out by the Maluku Provincial Government and the relationship patterns that need to be built through the Maluku Provincial Government's public policies towards indigenous peoples so that dynamic interactions can be established in an effort to accelerate the spread of the virus. Covid 19 at the local level. The research was conducted using the Social Legal Research method. Approach the problem using a statutory approach, and concepts. The results of this study found that the Maluku Provincial Government has carried out its responsibilities in fulfilling the right to information, education and health services to indigenous peoples, but it is still not optimal. Likewise, a public policy framework that favors the interests of indigenous peoples as a form of protection for the vulnerability of indigenous peoples from the dangers of the spread of the Covid-19 virus is also not optimal. The Maluku Provincial Government needs to formulate a formulation of a public policy framework that is oriented towards the goal of fulfilling the basic rights of indigenous peoples during the Covid-19 pandemic. The vulnerability of indigenous peoples needs to be protected with the political will of the Maluku Provincial government through budget politics, preparation of human and material resources and infrastructure that supports performance achievement in fulfilling the right to information, education and health services to indigenous peoples at the local level.